Robot X 2022: development of an object delivery system of USV - Sim, Bing Rui (Nanyang Technological University, 2022)
Maritime RobotX Challenge consists of various autonomous challenges with an emphasis on science and cooperative autonomy. Singapore is a country that flourishes based on its maritime port, autonomous systems that improve maritime capabilities are of great interest. For the project, a robotic arm and UAV platform are developed to accomplish an autonomous delivery system of an object. The system would include perception, mobility, and manipulation functionalities to complete the task of object delivery. Having an object delivery system, the project capabilities can be further extended into commercial systems. With the development of industrial 4.0, the autonomous systems could be used in the warehouse to deliver inventories or aid in the automation of food delivery or parcels services. Therefore, there is great potential in the development of autonomous delivery systems.